Ketimpangan Ekonomi Jawa dan Luar Jawa dan Perkembangan Perdagangan Antarpulau di Indonesia - Rinardi, Haryono; Indrahti, Sri; Masruroh, Noor Naelil (Jurnal Sejarah Citra Lekha, 2023)
This article discusses the relationship between economic inequality in Java and outer Java and its relationship with inter-island shipping and trade. By using the historical method, this study proves that economic inequality has been happening since the colonial until the independence period. This inequality arose because the role played by Java in its economic relations with outer Java became very dominant and decisive. Java became a kind of intermediary in economic relations outside Java with the international world. This role has occurred since the colonial period and did not change until independence. Java provides added value to commodities from outside Java, which are then resold to international markets. Therefore, Java has always had an advantage in economic relations with outer Java. This situation created economic disparities in relation to provincial regional income in present-day Indonesia.